(untitled) (Journal of Informatics and Mathematical Sciences, 2012)
In the present paper, we find the conditions to characterize projective change between two (α, β)-metrics, such as special (α, β)-metric, L=α-β^2α+β and Randers metric L= α+β on a manifold with dim n ≥ 3, where α and α are two Riemannian metrics, β and β are two non-zero 1-forms. Further, we study the special curvature properties of two classes of (α, β)-metrics.